TELAAH AJARAN TASAWUF AL-HALLAJ - Mohammad Ramdhany (UIN Sayyid Ali Rahmatullah Tulungagung, 2017)
Hulu>l is a polemical idea discussed in the world of Islamic Tasawuf or Sufism since 3rd century of Islamic history. This issue continued to be debated from time to time until today. Hulu>l or Oneness of the Absolute Existent had made conflict between Muslim scholars. The doctrine of hulu>l asserts that everything that exists can only exist because it is an aspect of Divine Reality, hence an aspect of Divine Unity itself. However, Sufi scholars assert that although hulu>l may be interpreted that Sufism sees the face of God everywhere, it does not mean that it has reduced God to everything. Some scholars become the supporters of this theory and some against this idea. One of the important figures related to this term was al-Hallaj. Al-Husayn ibn Mansur al-Hallaj was a controversial writer and teacher of Islamic mysticism. He is famous for his martyrdom for heresy at the hands of the Abbasid rulers which arousing admiration in some and repression on the others. The drama of his life and death has been considered a reference point in the history of Sufism. However, hulu>l still being discussed and debated to date and we can still find many people in many kinds of group whether they agree or against; understand its deeper meanings or just its literal. Keywords: al-Hallaj, tasawuf, hulu>l